Odpowiedzi

2009-11-30T16:41:41+01:00
A) 2x²-x+14x-7= 2x²+12x-7
b)2a²+8a-a-4= 2a²-7a-4
c)8a-12a²-2+3a=-12a²+11a-2
1 3 1
2009-11-30T16:44:11+01:00
A) (x+7)(2x-1)=2x²-x+14x-7=2x²+13x-7
b) (2a-1)(a+4)=2a²+8a-a-4=2a²+7a-4
c) (4a-1)(2-3a)=8a-12a²-2+3a=11a-12a²-2
d) (x +√5)(x-√5)=x²-√5x+√5x-5=x²-5
e) (2y - √3)(y+1)=2y²+2y-√3y-√3
f) (a+√2)(a-√3)=a²-√3a+√2a-√6=a²-√a
g) (2√2+k)(√2-k)=4+2√2k+√2k-k²=4+3√2k-k²
2009-11-30T16:57:04+01:00
A) (x+7)(2x-1)= 2x²-x+14x-7= 2x²+13x-7
b) (2a-1)(a+4)= 2a²+8a-a-4= 2a²+7a-4
c) (4a-1)(2-3a)= 8a-12a²-2+3a=11a-12a²-2
d) (x +√5)(x-√5)= x²-√5x+√5x-5= x²-5
e) (2y - √3)(y+1)= 2y²+2y-√3y-√3
f) (a+√2)(a-√3)= a²-√3a+√2a-√6= a²-√a
g) (2√2+k)(√2-k)= 4+2√2k+√2k-k²= 4+3√2k-k²